Enzymatic deglycation of Amadori products in bacteria: mechanisms, occurrence and physiological functions - Deppe, Veronika Maria; Bongaerts, Johannes; O'Connell, Timothy; Maurer, Karl-Heinz; Meinhardt, Friedhelm (Applied microbiology and biotechnology, 2011)
Amadori products (fructosamines)--ubiquitously occurring in nature--are precursors of the toxic and cell damaging ‘advanced glycation endproducts'; thus, it is not surprising that numerous organisms have developed systems to degrade such compounds. The deglycating enzymes differ with respect to their mechanisms as well as to their substrate specificities. Furthermore, different physiological functions are proposed for the different enzymes. The fructosamine 3-kinases of mammals and homologous proteins (fructosamine 3-kinase related proteins), which are common to all taxa, are thought to focus on intracellular repair functions. In contrast, in Bacillus subtilis and Escherichia coli, the cooperative action of a kinase and a deglycase facilitates Amadori degradation. As genes encoding these enzymes are co-transcribed with ABC transporter genes, it is thought that these genes facilitate the utilisation of extracellular Amadori products. Indeed, it has been shown that fructosamines can serve as the sole carbon and nitrogen sources. Here, we provide an overview of known deglycating systems with the emphasis on Amadori product degradation in bacteria.